Analisis Kasus Sengketa Tanah Waris Adat Dalam Putusan Mahkamah Agung No. 29 K/PDT/2004 - Rizkitiana, Ratu Amelia; Emiliyanti, Nabilla Lutfiah; Sabrina, Aryuni Fajriah; Hayya, Aisya Anjani Nurul; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
This research examines the Supreme Court Decision No. 29 K/Pdt/2004 concerning a land inheritance dispute in Bali, focusing on the application of Balinese customary inheritance law within the national legal framework. The dispute illustrates the complex interplay between customary law and state law, particularly in a society that adheres to a patrilineal kinship system. Employing a normative juridical approach and case study methodology, the research analyzes the Supreme Court's legal considerations in determining the rightful heirs and how customary law is accommodated within the ruling. The findings reveal the Court's recognition of the normative power of customary law and underscore the importance of respecting local values in dispute resolution. This study enhances the understanding of legal pluralism in Indonesia and highlights the significance of integrating customary law into the development of a fair and contextual legal system.